TINJAUAN YURIDIS TERKAIT PENERAPAN PRINSIP PENJUALAN PRODUK ASURANSI UNIT LINK DI INDONESIA - NIM. A1011201028, NOVIA AZMILA (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract Insurance is a contractual agreement between an insurance company and the insured, providing financial protection with the payment of a premium. Unit Link Insurance combines protection and investment, offering flexibility in premiums, protection, investment allocation, and withdrawals. Despite the positive outlook, the lack of understanding of investments and sales transparency is causing problems. The Insurance Victims Coordinator highlighted agents' lures that do not match reality. Strict supervision is needed to protect customers from risk and improve regulation of the application of Unit Link Insurance sales principles. In writing this thesis, the author uses normative research methods with the type of Normative Juridical approach, and the research technique is carried out with direct communication techniques, namely by conducting interviews with Mrs. Fitri as the Insurance Company Representative of PT AIA Financial which is the source of data of this thesis research. This research aims to find out how the application of the principle of selling unit-linked insurance products in Indonesia and whether it is in accordance with the regulations issued by the OJK. From the results of the research that has been done, although the state of sales of unit-linked insurance products in Indonesia shows a positive trend. Unit link insurance products in Indonesia show a positive trend, but there are still obstacles. constraints. These obstacles are found in many people who do not understand this product, causing problems related to the application of sales principles. This product, causing problems related to the application of sales principles. So that it can be Insurance companies are also working hard to improve the quality of their agents and service facilities for customers and prospective customers. Agents and service facilities for customers and prospective customers so that the obstacles in the process of selling Unit Link Products can run smoothly and the in the sales transaction process of the Unit Link Product can run smoothly and in accordance with OJK regulations, so that no more customers feel disadvantaged..Keywords: Customer Protection, Unit Link Insurance, Agent, Policy Abstrak Asuransi adalah perjanjian kontrak antara perusahaan asuransi dan tertanggung, memberikan perlindungan finansial dengan pembayaran premi. Asuransi Unit Link menggabungkan proteksi dan investasi, menawarkan fleksibilitas dalam premi, perlindungan, alokasi investasi, dan penarikan dana. Meski prospek positif, kurangnya pemahaman masyarakat terkait investasi dan transparansi penjualan menyebabkan permasalahan. Koordinator Korban Asuransi menyoroti iming-iming agen yang tidak sesuai dengan kenyataan. Diperlukan pengawasan ketat untuk melindungi nasabah dari risiko dan meningkatkan regulasi penerapan prinsip penjualan Asuransi Unit Link. Dalam penulisan skripsi ini penulis menggunakan metode penelitian normatif dengan jenis pendekatan Deskriptif-Normatif, dan teknik penelitian dilakukan dengan teknik komunikasi langsung yaitu dengan dilakukannya wawancara bersama Ibu Fitri selaku Perwakilan Perusahaan Asuransi PT AIA Financial yang menjadi sumber data dari penelitian skripsi ini. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan prinsip penjualan produk asuransi unit link di indonesia dan apakah telah sesuai dengan regulasi yang dikeluarkan oleh OJK. Dari hasil penelitian yang telah dilakukan, meski keadaan penjualan produk asuransi unit link di Indonesia menunjukkan tren positif, namun masih terdapat kendala. Kendala tersebut ialah terdapat pada banyak masyarakat kurang memahami produk ini, serta agen penjual asuransi yang terkadang juga sepenuhnya menguasai materi produk sehingga menimbulkan permasalahan terkait penerapan prinsip penjualan dalam Asuransi Unit Link. Namun kini, dapat terlihat bahwa kini Perusahaan-perusahaan Asuransi juga berupaya keras untuk meningkatkan kualitas para agen dan fasilitas layanan untuk nasabah dan calon nasabah agar kendala-kendala dalam proses transaksi penjualan Produk Unit Link tersebut dapat berjalan lancar dan sesuai dengan regulasi OJK, sehingga tidak ada lagitimbul masalah dan nasabah yang merasa dirugikan.. Kata Kunci: Perlindungan Nasabah, Asuransi Unit Link, Agen, Polis